ABÛ ISHÂQ IBRÂHÎM IBN MÛSÂ AL-SYÂTHIBÎ AND HIS OPINION ON THE DICHOTOMY OF ‘IBÂDÂT AND ‘ÂDÂT IN ISLAMIC LAW - Jamal Abdul Aziz (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
Abû Ishâq Ibrâhîm ibn Mûsâ al-Syâthibî (d. 790/1388), or who is known as al-Syâthibî, is one of the most famous fuqahâ’ in Maliki sect. When he was living in Granada in the thirteenth century, he faced a wide scale of social, economic, and cultural changes. At the same time, the teaching and practice of tasawwuf influenced the tendency of thinking of Islamic law. The big change supported him to formulate his philosophy of Islamic law. Mashlahah (mashâlih), as the main purpose of maqâshid al-syarî’ah, is the main concept of philosophy thinking in Islamic law that he built. The dichotomy of ‘ibâdât and ‘âdât contains the representation of fixed aspects which in one side is the teaching of worships (rites), and on the other side is the dynamic aspect from the Islamic law. ‘Ibâdât asked for a pure obedience from a human with the way has been specified by the God, while ‘âdât can receive any possible changes.Copyright (c) 2015 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.714